Genetic and Environmental Causes of Variation in the Difference Between Biological Age Based on DNA Methylation and Chronological Age for Middle-Aged Women. (3rd November 2015) - Li, Shuai; Wong, Ee Ming; Joo, JiHoon E.; Jung, Chol-Hee; Chung, Jessica; Apicella, Carmel; Stone, Jennifer; Dite, Gillian S.; Giles, Graham G.; Southey, Melissa C.; Hopper, John L.
Abstract : The disease- and mortality-related difference between biological age based on DNA methylation and chronological age (Δage) has been found to have approximately 40% heritability by assuming that the familial correlation is only explained by additive genetic factors. We calculated two different Δage measures for 132 middle-aged female twin pairs (66 monozygotic and 66 dizygotic twin pairs) and their 215 sisters using DNA methylation data measured by the Infinium HumanMethylation450 BeadChip arrays. For each Δage measure, and their combined measure, we estimated the familial correlation for MZ, DZ and sibling pairs using the multivariate normal model for pedigree analysis. We also pooled our estimates with those from a former study to estimate weighted average correlations. For both Δage measures, there was familial correlation that varied across different types of relatives. No evidence of a difference was found between the MZ and DZ pair correlations, or between the DZ and sibling pair correlations. The only difference was between the MZ and sibling pair correlations ( p < .01), and there was marginal evidence that the MZ pair correlation was greater than twice the sibling pair correlation ( p < .08). For weighted average correlation, there was evidence that the MZ pair correlation was greater than the DZ pair correlation ( p < .03), and marginally greater than twice the sibling pair correlation ( p < .08). The varied familial correlation of Δage is not explained by additive genetic factors alone, implying the existence of shared non-genetic factors explaining variation in Δage for middle-aged women.